2015
DOI: 10.5152/balkanmedj.2014.13230
|View full text |Cite
|
Sign up to set email alerts
|

The Approach of General Surgeons to Oncoplastic and Reconstructive Breast Surgery in Turkey: A Survey of Practice Patterns

Abstract: With the wide acceptance of Fisher's theory that breast cancer is a systemic disease from the start and in the light of improvements in adjuvant treatment, the role of surgery in the treatment of cancer was expected to gradually decrease (1). However today's surgical treatment of breast cancer has developed into oncoplastic and reconstructive surgery (Oncoplastic Breast Surgery (OBS) + Reconstructive Breast Surgery (RBS) = ORBS). Besides establishing ideal regional oncological control, surgeons are often faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…27,28 In Turkey, oncoplastic surgeries are performed successfully by general (breast) surgeons with or without plastic surgeons, and it is suggested that training in oncoplastic surgery be included in mainstream surgical training. 37 Indian researchers have proposed a "one surgeon, dual role" concept-in which one surgeon is trained to perform both the oncologic and plastic surgeryas a way to reduce the cost of care and make up for the dearth of plastic surgeons. 27 In fact, Oncoplastic surgeons in India and the United Kingdom have created a comprehensive, multidisciplinary Oncoplastic Surgery Training Program.…”
Section: Challenges To Breast Reconstruction Across the Globementioning
confidence: 99%
“…27,28 In Turkey, oncoplastic surgeries are performed successfully by general (breast) surgeons with or without plastic surgeons, and it is suggested that training in oncoplastic surgery be included in mainstream surgical training. 37 Indian researchers have proposed a "one surgeon, dual role" concept-in which one surgeon is trained to perform both the oncologic and plastic surgeryas a way to reduce the cost of care and make up for the dearth of plastic surgeons. 27 In fact, Oncoplastic surgeons in India and the United Kingdom have created a comprehensive, multidisciplinary Oncoplastic Surgery Training Program.…”
Section: Challenges To Breast Reconstruction Across the Globementioning
confidence: 99%